Dacryops with dacryolithiasis in a dog. Issue 5 (6th June 2022) - Susanti, Lina; Go, Seokmin; Go, Du‐Min; Woo, Sang‐Ho; Seo, Kangmoon; Kang, Seonmi
Abstract: Background: A 10‐year‐old castrated male Maltese dog was presented with chronic swelling that had been present for at least 5 years in the medial canthus of the right eye (OD). Objectives: To describe the treatment outcome of dacryops with dacryolithiasis. Methods: Bilateral patency of the nasolacrimal system was confirmed by flushing of both upper and lower puncta. Ocular ultrasonography revealed a well‐defined, oval‐shaped, heterogeneous mass with several hyperechoic foci. Dacryocystorhinography revealed no connection between the mass and lacrimal canaliculus. Gentle blunt dissection of the fibrous connective tissue around the cystic mass was performed. The mass was removed, which intraluminally contained multiple calculi. Results: Histopathologically, the cystic structure was lined by simple cuboidal epithelium and surrounded by smooth muscle actin positive myoepithelial cells consistent with dacryops derived from the lacrimal glandular ductal system. In addition, several spherical basophilic minerals were observed in the lumen, which were identified as dacryoliths. Conclusion: Surgical removal of this dacryops with dacryolithiasis was curative without recurrence after four months. Abstract : Dacryops containing dacryoliths were surgically removed from a 10‐year‐old Maltese dog. The cyst was confirmed through histopathology and immunohistochemistry to be derived from the lacrimal glandular ductal system, making this the first report of dacryops with dacryoliths in dogs. Nasolacrimal flushing, ocular ultrasound and dacryocystorhinography were performed to confirm the diagnosis and plan the surgical procedure.